Icterohemorrhagic Leptospirosis in Infant: Clinical Case - Gennady A. Kharchenko; Olga G. Kimirilovа ("Paediatrician" Publishers LLC, 2021)
Background. The importance of timely leptospirosis diagnosis and treatment has increased due to sporadic children morbidity. It is crucial in order to prevent the complications and adverse outcomes development.Clinical Case Description. The data from literature and our own clinical observation of leptospirosis with benign outcome in infant (with kidney damage, purulent meningitis, hemorrhagic syndrome and congenital heart disorder) is presented.Conclusion. The description of leptospirosis symptoms and course in the child is presented in the form of analysis of the clinical setting for further medical education, including differential diagnostics with viral hepatitis.